A critical evaluation of the new cram‐down tool in Singapore's restructuring regime. Issue 2 (11th May 2021) - Teo Chuanzhong, Ken
Abstract: Singapore has recently reformed its insolvency regime in its efforts to be an international restructuring hub. To that end, Singapore has attempted to take an autochthonous approach in adapting several of the legal tools from the US Chapter 11 for reforming its own restructuring regime. This article seeks to critically evaluate the cross‐class cram‐down mechanism in Singapore, which has been implemented with caution and novelty. While such an approach seeks to protect both the interest of its shareholders and creditors, it might lead to a regime that is undesirable for Singapore, considering its pursuit to be an international restructuring hub. In particular, it will be argued that Singapore's cram‐down mechanism is susceptible to risks of hold‐ups by both shareholders and creditors. Additionally, from the ex ante perspective, the cram‐down mechanism does not promote expediency in parties' negotiation. The implementation of a novel cram‐down arrangement would also inextricably bring about uncertainty to its application. A lacklustre engagement of the cram‐down tool in practice might ensue, which could hamper Singapore's plan to organically develop and fine‐tune the cram‐down regime down the road.